Psychologic training program and mental toughness development: an integrative revision of literature - de Freitas Corrêa, Mariana (2023)
The Mental Toughness (MT) construct is considered an essential component of sports performance, therefore, it is important to examine how programs to develop MT are being offered and applied to athletes. In this sense, the objective of this study was to review the literature in relation to psychological training programs (PST) applied for the development of Mental Toughness in the sport context. The Scielo, PubMed, SportDiscus, BVS, Embase, and Psynet databases were used, considering the Portuguese, English and Spanish languages. The program EndNote® was used to store and organize the material. The inclusion criteria were full papers, with athletes, investigating the psychological training for MT development; the exclusion criteria were: review studies, studies of areas other than sports, and psychological training carried out with injured athletes. The results show 1.858 studies and, from this total, ten studies were included for synthesis and qualitative analysis. The findings show four studies used collective modalities, and seven used individual modalities, being four studies with adult athletes and six with teenager athletes. Concerning the structure of the programs, six studies used traditional PST activities, while two worked with specific activities to develop MT. For the pre and post-evaluation, all the ten studies used tools that measure MT. From the analysed studies, nine show an increase in MT scores after the interventions. In conclusion, the psychological training programs geared to developing the MT are not different from traditional PST programs, both in terms of the psychological skills worked on, the activities performed and the number of sessions.